EXCEPTIONAL INDIVIDUAL - TELFORD, CHARLES W.; SAWREY, J. M. (PRENTICE HALL INC., NEW JERSEY, 1977)
This book is intended for use at the upper division or graduate level as an introduction to the problems of exceptional people . etc...
Keywords: CHILD AND ADOLESCENT DEVELOPMENT